Profil kemampuan komunikasi peserta didik materi SPLDV - Djuniakh, Siti Wasillah; Effendi, Kiki Nia Sania (IKIP Siliwangi, 2024)
This research aims to find out and describe how high the mathematical communication skills of Grade IX Middle School (SMP) students are on the material Systems of Linear Equations in Two Variables (SPLDV). This study involved students in class IX-D at one of the State Middle Schools in Karawang Regency for the 2023/2024 academic year as research subjects. Purposive sampling technique was used to select subjects and obtained 32 students. Qualitative descriptive research was used. The data collection method was carried out using a mathematical communication ability evaluation tool which consisted of three descriptive questions. The data processing technique used descriptive statistics to determine the high, medium and low categories of all students in classes IX-D. It is proven from the result of the students’ mathematical communication skills test that they are in the low classification because they show an average score of 32,00957.